Daniił Andriejew jako pisarz mistyczny (рroblem samookreślenia pisarza) - Nowakowska, Jana (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
In this article we defined the aim of bringing closer Daniil Andreyev's personality which refers to the statements of the writer's self-identification. In conclusion, Andreyev is a mystical writer who thought about himself as a messenger, visionary, dualist, poet-magician and words seeker. Moreover, Andreyev considered himself as a creator who does not invent things, but only in the language of poetry describes the otherworldly. The mystical was not only present in his works, but also amounted to a component of his personality. Its foundations were reconstructed on a deep Orthodox faith influenced by the philosophy of Vladimir Solovyov, the poetry of Alexander Blok, the visions of Alexander Kovalensky as well as his individual mystical experience.